My Gay Middle Ages - Strouse, A.W (punctum books, 2015)
In the world of My Gay Middle Ages, Chaucer and Boethius are the secret-sharers of A.W. Strouse's "gay lifestyle." Where many scholars of the Middle Ages would "get in from behind" on cultural history, Strouse instead does a "reach around." He eschews academic "queer theory" as yet another tedious, normative framework, and writes in the long, fruity tradition of irresponsible, homo-medievalism (a lineage that includes luminaries like Oscar Wilde, who was sustained by his amateur readings of Dante and Abelard during the darks days of his incarceration for crimes of "gross indecency"). Strouse experiences medieval literature and philosophy as a part of his everyday life, and in these prose poems he makes the case for regarding the Middle Ages as a kind of technology of self-preservation, a posture through which to spiritualize the petty indignities of modern urban life. With a Warholian flair for insouciant name-dropping and a Steinian appetite for syntactic perversion, Strouse monumentalizes the medieval within the contemporary and the contemporary within the medieval.